2008
DOI: 10.4049/jimmunol.181.5.2980
|View full text |Cite
|
Sign up to set email alerts
|

FOXO1 Regulates L-Selectin and a Network of Human T Cell Homing Molecules Downstream of Phosphatidylinositol 3-Kinase

Abstract: In T cells, the PI3K pathway promotes proliferation and survival induced by Ag or growth factors, in part by inactivating the FOXO transcription factor 1. We now report that FOXO1 controls the expression of L-selectin, an essential homing molecule, in human T lymphocytes. This control is already operational in unprimed T cells and involves a transcriptional regulation process that requires the FOXO1 DNA-binding domain. Using transcriptional profiling, we demonstrate that FOXO1 also increases transcripts of EDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
175
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(187 citation statements)
references
References 44 publications
12
175
0
Order By: Relevance
“…KLF2 is a zinc-finger transcription factor that has a documented role in controlling naive T-cell migration patterns (12)(13)(14). Its expression is promoted by Foxo1, a PKB-regulated transcription factor that has also been reported to control T-cell circulation (9,10). Moreover, Foxo1 and Foxo3 promote Treg development and function; mice lacking these transcription factors have reduced percentages of FoxP3 + T cells (8), especially at 3 wk of age (7), and fail to develop functional Tregs.…”
Section: Resultsmentioning
confidence: 99%
“…KLF2 is a zinc-finger transcription factor that has a documented role in controlling naive T-cell migration patterns (12)(13)(14). Its expression is promoted by Foxo1, a PKB-regulated transcription factor that has also been reported to control T-cell circulation (9,10). Moreover, Foxo1 and Foxo3 promote Treg development and function; mice lacking these transcription factors have reduced percentages of FoxP3 + T cells (8), especially at 3 wk of age (7), and fail to develop functional Tregs.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have identified the transcription factor FOXO1 as a master regulator of CD62-L transcription, likely via the expression of KLF2. In quiescent T cells, active FOXO1 in the nucleus maintains expression of KLF2, which regulates the expression of CCR7 and CD62-L (15)(16)(17)(21)(22)(23)(24)(25)(26). However, mycolactone reduced the transcription of CD62-L without modulating the expression of KLF2 (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…5B). This inhibition was detectable after 4 h and persisted until 20 h. Because CD62-L gene expression is controlled in human T cells by the Forkhead box O 1 (FOXO1)/ Kruppel-like factor 2 (KLF2) transcriptional axis, the expression of KLF2 was also examined (15)(16)(17). KLF2 was not modulated in mycolactone-exposed T cells (Fig.…”
Section: Mycolactone-treated T Cells Have Impaired Homing Capacity Andmentioning
confidence: 99%
“…Is this sufficient to cause loss of Foxo transcriptional activity? In quiescent normal lymphocytes, nonphosphorylated transcriptionally active Foxos control expression of Kruppellike factor 2 (KLF2), a transcription factor that regulates expression of the chemokine receptor CCR7 and the adhesion receptor CD62L that together control T cell transmigration from the blood across high endothelial venules into secondary lymphoid tissues (Carlson et al, 2006;Bai et al, 2007;Fabre et al, 2008;Sebzda et al, 2008;Sinclair et al, 2008;Kerdiles et al, 2009). The expression of these receptors is also controlled by mTOR signaling (Sinclair et al, 2008), which is also triggered by PTEN loss.…”
Section: Pten Deletion Disrupts Expression Of a Network Of Adhesion Mmentioning
confidence: 99%
“…The PDK1-PKB signaling axis is fundamentally important for normal thymocytes because it regulates protein synthesis, cell growth, and cell cycle progression via control of glycolysis and nutrient uptake (Rathmell et al, 2003;Plas and Thompson, 2005;Cornish et al, 2006;Kelly et al, 2007). PI(3,4,5)P 3 signaling via mammalian target of rapamycin (mTOR) and Foxo family transcription factors also controls lymphocyte trafficking by determining the repertoire of adhesion and chemokine receptors expressed by T lymphocytes (Fabre et al, 2008;Sinclair et al, 2008;Kerdiles et al, 2009). …”
mentioning
confidence: 99%